PSS cost engineering: A model-based approach for concept design. (May 2020) - Bertoni, Alessandro; Bertoni, Marco
Abstract: Manufacturing companies are increasingly moving toward delivering combinations of products and services to provide higher value to their customers. The development of such Product Service Systems (PSS) escalates in complexity when several products developed by different suppliers need to be integrated into a unique system. For first tier suppliers, it is a great challenge to model and simulate the impact of changing design variables at the micro-level on both hardware properties and governing behaviors of services over the entire life-cycle of the PSS. The paper describes a model-based approach developed to estimate the life cycle cost of a PSS hardware already at a concept design stage. The proposed approach computes the relative cost efficiency of a set of design variants using as input the data generated by the simulations run in the Computer Aided Engineering (CAE) environment. The approach allows the exploration of the design space of a PSS given by the variation of the geometry of a Computer Aided Design (CAD) model, building on the computation of customized cost modules selected by a generic list of PSS cost dimensions. For each evaluated design case, the model produces as output a unique monetary figure of the cost expected to incur by owning or using the asset throughout the lifetime. The work has been conducted in collaboration with a tier-one aerospace component manufacturer, and the application of the model is exemplified through a case study related to the development of a turbine rear structure (TRS) for commercial jet engines. The approach is most suitable for the development of complex systems in which new products and components are integrated into a shared product platform. The results are discussed in relation to the current literature on PSS cost engineering, highlighting challenges to be addressed to increase cost estimation accuracy and increase uncertainty identification and awareness.